The Effect of Diabetes on Prognosis Following Myocardial Infarction Treated with Primary Angioplasty and Potent Antiplatelet Therapy - Simek, Stanislav; Motovska, Zuzana; Hlinomaz, Ota; Kala, Petr; Hromadka, Milan; Knot, Jiri; Varvarovsky, Ivo; Dusek, Jaroslav; Rokyta, Richard; Tousek, Frantisek; Svoboda, Michal; Vodzinska, Alexandra; et al. (Journal of clinical medicine, 2020)
PURPOSE: To investigate the prognostic significance of diabetes mellitus (DM) in patients with high risk acute myocardial infarction (AMI) treated with primary percutaneous coronary intervention (pPCI) in the era of potent antithrombotics. METHODS: Data from 1230 ST-segment elevation myocardial infarction (STEMI) patients enrolled in the PRAGUE-18 (prasugrel vs. ticagrelor in pPCI) study were analyzed. Ischemic and bleeding event rates were calculated for patients with and without diabetes. The independent impact of diabetes on outcomes was evaluated after adjustment for outcome predictors. RESULTS: The prevalence of DM was 20% (N = 250). Diabetics were older and more often female. They were more likely to have hypertension, hyperlipoproteinemia, multivessel coronary disease and left main disease, and be obese. The primary net-clinical endpoint (EP) containing death, spontaneous nonfatal MI, stroke, severe bleeding, and revascularization at day 7 occurred in 6.1% of patients with, and in 3.5% of patients without DM (HR 1.8; 95% CI 0.978-3.315; P = 0.055). At one year, the key secondary endpoint defined as cardiovascular death, spontaneous MI, or stroke occurred in 8.8% with, and 5.5% without DM (HR 1.621; 95% CI 0.987-2.661; P = 0.054). In those with DM the risk of total one-year mortality (6.8% vs. 3.9% (HR 1.773; 95% CI 1.001-3.141; P = 0.047)) and the risk of nonfatal reinfarction (4.8% vs. 2.2% (HR 2.177; 95% CI 1.077-4.398; P = 0.026)) were significantly higher compared to in those without DM. There was no risk of major bleeding associated with DM (HR 0.861; 95% CI 0.554-1.339; P = 0.506). In the multivariate analysis, diabetes was independently associated with the one-year risk of reinfarction (HR 2.176; 95% Confidence Interval, 1.055-4.489; p = 0.035). CONCLUSION: Despite best practices STEMI treatment, diabetes is still associated with significantly worse prognoses, which highlights the importance of further improvements in the management of this high-risk population.